Oncogenic micro-RNAs and Renal Cell Carcinoma - Grange, Cristina; Collino, Federica; Tapparo, Marta; Camussi, Giovanni (Frontiers in Oncology, 2014)
Tumor formation is a complex process that occurs in different steps and involves many cell types, including tumor cells, endothelial cells, and inflammatory cells, which interact to promote growth of the tumor mass and metastasization. Epigenetic alterations occurring in transformed cells result in de-regulation of miRNA expression (a class of small non-coding RNA that regulates multiple functions) which contributes to tumorigenesis. The specific miRNAs, which have an aberrant expression in tumors, are defined as oncomiRNAs, and may be either over- or under-expressed, but down-regulation is most commonly observed. Renal cell carcinoma is a frequent form of urologic tumor, associated with an alteration of multiple signaling pathways. Many molecules involved in the progression of renal cell carcinomas, such as HIF, VEGF or mTOR, are possible targets of deregulated miRNAs. Within tumor mass, the cancer stem cell population is a fundamental component that promotes tumor growth. The cancer stem cell hypothesis postulates that cancer stem cells have the unique ability to self-renew and to maintain tumor growth and metastasis. Cancer stem cells present in renal cell carcinoma were shown to express the mesenchymal stem cell marker CD105 and to exhibit self-renewal and clonogenic properties, as well as the ability to generate serially transplantable tumors. The phenotype of cancer stem cell has been related to the potential to undergo the epithelial-mesenchymal transition, which has been linked to the expression pattern of tumorigenic miRNAs or down-regulation of anti-tumor miRNAs. In addition, the pattern of circulating miRNAs may allow discrimination between healthy and tumor patients. Therefore, a miRNA signature may be used as a tumor biomarker for cancer diagnosis, as well as to classify the risk of relapse and metastasis, and for a guide for therapy.